2019
DOI: 10.1021/acs.langmuir.9b01425
|View full text |Cite
|
Sign up to set email alerts
|

Poly(4-vinylaniline)/Polyaniline Bilayer-Functionalized Bacterial Cellulose for Flexible Electrochemical Biosensors

Abstract: Bacterial cellulose (BC) nanofibril network is modified with an electrically conductive polyvinylaniline/polyaniline (PVAN/PANI) bilayer for construction of potential electrochemical biosensors. This is accomplished through surface-initiated atom transfer radical polymerization of 4-vinylaniline, followed by in situ chemical oxidative polymerization of aniline. A uniform coverage of BC nanofiber with 1D supramolecular PANI nanostructures is confirmed by FTIR, XRD and CHN elemental analysis. Cyclic voltammogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…The dense structure of BC networks has pores whose sizes are not large enough to allow migration. Supplementation of other materials such as silk fibroin (SF) increased pore size and subsequently, induced a significant increase in cell adhesion and cell viability in comparison with pure BC [ [106] , [107] , [108] ]. Cai et al.…”
Section: Application Of Other Scaffold Materials In Endometrial Regenerative Medicinementioning
confidence: 99%
“…The dense structure of BC networks has pores whose sizes are not large enough to allow migration. Supplementation of other materials such as silk fibroin (SF) increased pore size and subsequently, induced a significant increase in cell adhesion and cell viability in comparison with pure BC [ [106] , [107] , [108] ]. Cai et al.…”
Section: Application Of Other Scaffold Materials In Endometrial Regenerative Medicinementioning
confidence: 99%
“…After 7 days of culture, the SVZ cells differentiated into specialized and mature neurons with long neurites measuring up to 115 ± 24 μm in length. [128] Random and aligned conductive nanofibers composed of poly (lactic acid) (PLA) and Ppy were fabricated via electrospinning to investigate the synergetic effects of topographical features and electrical properties on differentiation of PC12 cells. In order to provide a better microenvironment for cell attachment and neurite outgrowth, the hydrophobicity of nanofibers surface was boosted by poly-ornithine coating.…”
Section: Surface Topography and Electrical Signals Co-effects On Neural Differentiation Of Stem Cellsmentioning
confidence: 99%
“…When Graphene/Carbon Nanotube/Bacterial Cellulose (RGO/CNT/BC) architecture was designed as substrate for loading polypyrrole (PPy), Bai et al [116] showed that flexible supercapacitor exhibits stable electrochemical performance under bending and flat conditions. Similarly, Rebelo et al [117] synthesized an electrically conductive BC/Polyvinylaniline/ Polyaniline (BC/PVAN/PANI) nanobiosensor for potential use in nerve regenerative medicine, which demands both electroactivity and biocompatibility. BC has also become a valuable for production of lithium-ion batteries (LIB).…”
Section: Electronic Electrochemical and Magnetic Field 1321 Worldmentioning
confidence: 99%